Tax morale and reciprocity: A case study from Vietnam - Björn Jahnke (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
Understanding the effects of reciprocity on tax morale is crucial to explain tax compliance behavior. However, there is only little research about which sources of reciprocity affect tax morale most. Thus, this paper for the first time gauges the effects from two sources of reciprocity on tax morale in an empirical study. The first source, vertical reciprocity, measures how tax payers value their contributions to the government. The second source, horizontal reciprocity, examines the impact of the perceived compliance behavior of other tax payers. The focus of the study is on Vietnam. The country seems to be a promising spot for this type of research because it exhibits an exceptional high level of tax morale and collectivism but only has low tax audit probabilities. This analysis is based on a consumer survey in the City of Hue which combines and extends questions from previous versions of the European and the World Value Survey. The result shows that both reciprocity measures are significantly correlated with tax morale but that vertical reciprocity prevails.
Keywords: D79; H26; Z13; 330; Tax morale; Tax compliance; Tax evasion; Reciprocity